Reklamos vertimo būdai Latvijoje ir jų vertimo poveikis latvių kalbai - Ločmele, Gunta (Vertimo studijos, 2021)
A range of factors such as brand type, brand positioning and the target culture’s attitude to global brands influence the translation of advertisements. There are various kinds of adaptation in advertisement translations: adaptation by replacement, by omission, by sentence-structure change and by addition. Advertisements may be translated literally, by a synonym, by glocalisation and abstraction change. In other cases, the text in the original is simply replaced. Translated texts of all types of brands are characterised by borrowings and a calqued sentence structure, and these in turn penetrate the Latvian language. Under the influence of English, fashion words enter Latvian from translations. Brands, and translations of texts defined by them, determine the peculiarities of Latvian in advertising.